Correlates of social isolation among people living with HIV in British Columbia, Canada. Issue 5 (4th May 2021) - Marziali, Megan E.; Card, Kiffer G.; McLinden, Taylor; Closson, Kalysha; Wang, Lu; Trigg, Jason; Salters, Kate; Lima, Viviane D.; Parashar, Surita; Hogg, Robert S.
ABSTRACT: Our study aims to define and identify correlates of social isolation among people living with HIV (PLHIV). The Longitudinal Investigation into Supportive and Ancillary health services (LISA) study provided a cross-sectional analytic sample of 996 PLHIV in British Columbia, Canada (sampled between 2007 and 2010). Individuals marginalized by socio-structural inequities were oversampled; sampling bias was addressed through inverse probability of participation weighting. Through latent class analysis, three groups were identified: Socially Connected (SC) ( n = 364, 37%), Minimally Isolated (MI) ( n = 540, 54%) and Socially Isolated (SI) ( n = 92, 9%). Correlates of the SI and MI classes, determined through multivariable multinomial regression using the SC class as a reference, include: recent violence (aOR 1.61, 95%CI 1.28–2.02 [MI vs. SC]; aOR 2.04, 95%CI 1.41–2.96 [SI vs. SC]) and a mental health diagnosis (aOR 1.50, 95% CI 1.31–1.72 [MI vs. SC]; aOR 1.43, 95%CI 1.11–1.83 [SI vs. SC]). Women (aOR 0.47; 95%CI 0.32–0.68 [SI vs. SC]), individuals of Indigenous ancestry (aOR 0.59; 95%CI 0.40–0.87 [SI vs. SC]) and people identifying as gay or lesbian (aOR 0.37; 95%CI 0.26–0.52 [SI vs. SC]) were less likely to experience isolation. These findings highlight the importance of supporting communities fostering connectedness and identifies populations susceptible to isolation.